IMPLEMENTATION OF MONTESSORI ACTIVITY-BASED LEARNING IN MALAYSIA: TEACHERS’ RETROSPECTIVE - Padmany Gonaseran; Mohd Nazri Abdul Rahman (P3I UMSurabaya, 2024)
The research investigates how Malaysian kindergarten teachers apply the Montessori activity-based learning approach. Using qualitative methods, researchers interviewed three female educators between 30-35 years old, who had taught for 1-4 years. Results indicated that teachers viewed the Montessori approach favourably, noting its positive impact on children's growth across various domains including practical skills, sensory development, mathematical understanding, linguistic abilities, and cultural awareness. The study also identified several obstacles, including limited parent understanding, varying student requirements, and inadequate professional development opportunities. A significant challenge emerged from parents' expectations and misunderstandings, with some expressing concern about reduced focus on conventional academic exercises, particularly writing tasks. The research emphasizes several requirements: ongoing teacher education and programs to inform parents. The study suggests implementing more comprehensive professional development, adopting varied assessment strategies, and organizing parent education sessions to enhance understanding of Montessori principles.